Patterns of Parental Rearing Styles and Child Behaviour Problems among Portuguese School-Aged Children - Pereira, Ana I. F. (2008)
The majority of studies investigating the effects of parental behaviour on the child’s adjustment have a dimensional approach. We identified the existence of various patterns in parental rearing styles and analysed the relationship between different parenting patterns and behavioural problems in a group of school-aged children. A longitudinal, multi-informant study was conducted. The sample consisted of 519 school-aged children from the Portuguese general population. Parental rearing styles were measured using the EMBU-C, a questionnaire that evaluates children’s perception of parental rearing dimensions. The assessment of child behavioural problems included the evaluation of internalizing and externalizing problems, and data from multiple reporters (parents and teacher). One year later, after a school transition, the adjustment of a sub-sample of 220 children was evaluated again. Cluster analysis identified four types of parental rearing styles: low support, supportive-controller, rejecting-controller, and supportive. In both assessment periods, low support and rejecting-controller parenting patterns showed higher levels of behavioural problems than the supportive and supportive-controller parenting patterns. These patterns show significant differences between them regarding behavioural problems and have a higher predictive value regarding externalizing problems (versus internalizing problems).